2023
DOI: 10.3390/v15041027
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Opioid Fentanyl Increases HIV Replication and Chemokine Co-Receptor Expression in Lymphocyte Cell Lines

Abstract: Background: In the United States, the illicit use of synthetic opioids such as fentanyl has led to a serious public health crisis. Synthetic opioids are known to enhance viral replication and to suppress immunologic responses, but their effects on HIV pathogenesis remain unclear. Thus, we examined the impact of fentanyl on HIV-susceptible and HIV-infected cell types. Methods: TZM-bl and HIV-infected lymphocyte cells were incubated with fentanyl at varying concentrations. Expression levels of the CXCR4 and CCR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Several studies have reported that specific opioids could enhance HIV infectivity and replication through the upregulation of HIV co-receptors and impairment of intracellular innate antiviral responses [ 11 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These findings may explain in vivo observations of a higher frequency of HIV founder viruses following intravenous opioid exposure and greater CD4 T-cell loss and viral set-point in macaques infected with the simian immunodeficiency virus (SIV) and undergoing long-term morphine administration [ 11 ].…”
Section: Opioids and Hiv Infectivity And Replicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported that specific opioids could enhance HIV infectivity and replication through the upregulation of HIV co-receptors and impairment of intracellular innate antiviral responses [ 11 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These findings may explain in vivo observations of a higher frequency of HIV founder viruses following intravenous opioid exposure and greater CD4 T-cell loss and viral set-point in macaques infected with the simian immunodeficiency virus (SIV) and undergoing long-term morphine administration [ 11 ].…”
Section: Opioids and Hiv Infectivity And Replicationmentioning
confidence: 99%
“…Morphine, fentanyl, buprenorphine, and methadone may variably enhance CCR5 and CXCR4 expression in different cell types [ 11 , 32 , 33 , 36 , 37 ]. Methadone might even downregulate the natural chemokine competing for CCR5 (MIP-1b) in macrophages [ 34 ].…”
Section: Opioids and Hiv Infectivity And Replicationmentioning
confidence: 99%
See 2 more Smart Citations